REDUCTION OF OPERATIONAL WASTE: a study in an aeronautical industry - Sinibaldi, Mariana da Silva; Junior, Marco Antônio Alves de Souza (Revista Interface Tecnológica, 2021)
The competitive market has demanded from companies a greater dedication to actions aimed at increasing productivity even with limited resources. For this, companies need to continuously improve their production processes. The Toyota Production System, in order to add value to the processes, assists companies in these improvements, making them capable of identifying and eliminating waste through methodologies and problem solving tools. This article aims to address, in the form of a bibliographic review, the concepts of the Toyota Production System and how it helps in the production chain. Then the focus is given on a case study, using the qualitative research methodology, highlighting how the application of Lean Manufacturing in an aeronautical company helps to increase productivity and reduce operating costs, maximizing the progress of the results of the company. Through the studies carried out in this research, it can be concluded that the Toyota Production System can bring numerous competitive advantages to organizations.
Keywords: Toyota Production System; Just In Time; Kaizen